Gamifikasi dan Mentimeter: Mewujudkan English Learning yang Lebih Menarik dan Interaktif - Samad, Pratiwi; Abbas, Moh. Jenli (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Gamification in English language learning along with the use of Mentimeter is essential for enhancing educational capabilities in English for students at SMP Negeri 1 Duhiadaa. This research aims to improve students' proficiency and engagement in learning English. A qualitative research method was used with interviews as the primary instrument. The third-grade students were the population and 10 students were selected through purposive sampling. The results showed that learners were actively engaged in their English quizzes, enjoying the use of gamification tools like Duolingo and Quizwhizzer. The integration of gamification platfoms, such as Duolingo and Quizwhizzer, combined with Mentimeter, significantly boosts students' engagement and learning capabilities in English. This approach not only engages students in interactive learning but also motivates them with new experience